TAX COLLECTION DIGITALIZATION, BLOCKCHAIN TECHNOLOGY, AND FOREIGN EXCHANGE MARKET STABILITY: IMPLICATIONS FOR MODERN TAX POLICY - Andaru Dwi Drestanta; Imam Mualim; Muhammad Ali Maskur (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2025)
Abstract The rapid advancement of digital technologies has fundamentally transformed tax administration and global financial systems, creating new opportunities to enhance transparency, efficiency, and regulatory compliance. Despite the growing adoption of digital taxation platforms, limited empirical attention has been given to the integrated relationship between tax digitalization, blockchain technology, foreign exchange (forex) market dynamics, and the behavioral financial perspectives presented in The Psychology of Money. This study aims to examine the influence of tax digitalization, supported by blockchain technology and behavioral financial literacy, on tax policy development, forex market dynamics, and digital financial governance. A quantitative research design was employed using secondary data obtained from tax authority reports, Bloomberg foreign exchange statistics, macroeconomic indicators, and literature related to The Psychology of Money. Complementary primary data were collected through questionnaire surveys measuring perceptions of digital tax adoption and blockchain integration. The data were analyzed using descriptive statistics, correlation analysis, multiple linear regression, and Vector Autoregression (VAR) to investigate both cross-sectional and dynamic relationships among the variables. The findings indicate that tax digitalization significantly improves administrative efficiency, transparency, and tax compliance, while blockchain technology strengthens transaction security, accountability, and fraud prevention within tax administration. Furthermore, monetary and fiscal policy adjustments associated with digital tax reforms influence forex market stability and contribute to the growing adoption of digital assets. The study also highlights that behavioral financial literacy, as conceptualized in The Psychology of Money, supports more adaptive financial decision-making in response to digital economic transformation. These findings provide practical implications for policymakers in designing integrated digital tax systems and contribute theoretically to the literature on digital taxation, blockchain governance, and behavioral finance in the era of financial digitalization.